ChREBP-Mediated Regulation of Lipid Metabolism: Involvement of the Gut Microbiota, Liver, and Adipose Tissue - Iizuka, Katsumi; Takao, Ken; Yabe, Daisuke (Frontiers in Endocrinology, 2020)
Carbohydrate response element-binding protein (ChREBP) plays an important role in the development of type 2 diabetes, dyslipidemia, and non-alcoholic fatty liver disease, as well as tumorigenesis. ChREBP is highly expressed in lipogenic organs, such as liver, intestine, and adipose tissue, in which it regulates the production of acetyl CoA from glucose by inducing Pklr and Acyl expression. It has recently been demonstrated that ChREBP plays a role in the conversion of gut microbiota-derived acetate to acetyl CoA by activating its target gene, Acss2, in the liver. ChREBP regulates fatty acid synthesis, elongation, and desaturation by inducing Acc1 and Fasn, elongation of long-chain fatty acids family member 6 (encoded by Elovl6), and Scd1 expression, respectively. ChREBP also regulates the formation of very low-density lipoprotein by inducing the expression of Mtp. Furthermore, it plays a crucial role in peripheral lipid metabolism by inducing Fgf21 expression, as well as that of Angptl3 and Angptl8, which are known to reduce peripheral lipoprotein lipase activity. In addition, ChREBP is involved in the production of palmitic-acid-5-hydroxystearic-acid, which increases insulin sensitivity in adipose tissue. Curiously, ChREBP is indirectly involved in fatty acid β-oxidation and subsequent ketogenesis. Thus, ChREBP regulates whole-body lipid metabolism by controlling the transcription of lipogenic enzymes and liver-derived cytokines.